Windswept and deposition - Klassen, Jaclyn, artist (Colorado State University. Libraries, 2017)
The artist's statement: There is an importance to me in clay with its ability to speak of weight, human and geologic history, and stillness. These aspects of clay, which have grabbed my attention in such a way as demand inquiry, underpin much of my work. Stillness, weight, and the gravity of things echo through my work and in my memory as a sunny afternoon when still quite a young child. I am sitting on the ground, alone in my sister's room playing with her necklace. This necklace is of the lightest silver, yet I recall its weight. I lift it and let it fall, over and over, curling into my palm. Never once does it fall the same. It is always revealing itself anew through movement, texture, and weight.
Jaclyn Klassen: capstone
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: ceramic; sculpture; yellow